Genetic influences on sleep duration and overlap with personality - Butković, Ana; Vukasović, Tena; Bratko, Denis (2012)
There are only a few studies available that have explored genetic influences on sleep duration. Results on large Finish and Australian samples indicate that around 40% of individual differences in sleep duration could be attributed to genetic differences, but heritability of sleep duration in UK sample was 0%. Also, familial aggregation of sleep duration on Taiwanese sample of parents and their children was close to zero. Correlations between sleep duration and personality traits were found to be low in most studies, but some studies have found positive relationship with conscientiousness and negative with neuroticism. This study explores the relationship between sleep duration and personality traits within behavioral genetic perspective. Data on average sleep duration during the night and five-factor personality traits were collected from 339 twin pairs (105 MZ and 234 DZ) aged between 15 and 22 years. Univariate results indicated that genetic factors contributed between 40-60% to individual differences in personality, and around 60% for sleep duration. Significant, but low phenotypic correlations were obtained for sleep duration with neuroticism (r= -.14) and openness (r= -.16). Bivariate results indicated that these phenotypic correlations were mainly due to overlapping genetic factors.
42nd Annual Meeting of the Behavior Genetics Association (22.-25.06.2012. ; Edinburgh, Ujedinjeno Kraljevstvo)
Projekt MZOS
ENG